Fixed Point Theorems for Multivalued Nonself G -Almost Contractions in Banach Spaces Endowed with Graphs - J. Tiammee (2018)
© 2017 J. Tiammee et al. In this paper, we prove some fixed point theorems for multivalued nonself G-almost contractions in Banach spaces with a directed graph and give some examples to illustrate our main results. The main results in this paper extend and generalize many known results in the literature therein.